Aplicación del score MELD sodio en pacientes diagnosticados con cirrosis alcohólica del Hospital General Isidro Ayora Loja - Jiménez Loaiza, Michelle Alejandra (2020)
Alcoholic liver cirrhosis is a clinical condition characterized by chronic irreversible anatomic and functional alteration of the liver parenchyma secondary to excessive alcohol consumption. This disease is linked to a high mortality rate in relation to the degree of liver involvement and its definitive treatment will require a liver transplant, which is why the present descriptive, prospective, and cross-sectional study is carried out to estimate survival to three months by applying the sodium MELD score that evaluates laboratory parameters including the measurement of sodium ion, whose deficit (<130 mEq/L) is considered as a negative predictive factor of survival in the cirrhotic patient. In 2018, twenty-six adult patients diagnosed with alcoholic cirrhosis who were admitted to the Isidro Ayora Hospital in Loja were evaluated. 38.5% (n=10) presented a probability of mortality at 3 months of 6%, followed by a probability of mortality of 19.6% to 36.6% (n=9). Being 100% male sex and predominant age group of 51-60 years with 38.5% (n=10). BMI in 33.7% (n=9) was normal. There were no associated viral liver infections. The most common complication was ascites in 79.2% (n = 19). 26.9% (n=7) died within the first three months, of which three obtained a mortality rate of 19.6% followed by a 52.6% percentage in the rest. Being able to consider the sodium MELD score an adequate predictor of mortality. Key words: Mortality Prognosis, Sodium, Ascites, Liver Transplantation.